Combining Immune Checkpoint Inhibitors With Conventional Cancer Therapy - Yan, Yiyi; Kumar, Anagha Bangalore; Finnes, Heidi; Markovic, Svetomir N.; Park, Sean; Dronca, Roxana S.; Dong, Haidong (Frontiers in Immunology, 2018)
Immune checkpoint inhibitors targeting the immunosuppressive PD-1/PDL-1 pathway have recently revolutionized cancer treatment, providing unprecedented clinical benefits. However, primary or acquired therapy resistance can affect up to two-thirds of patients receiving immune checkpoint inhibitors, underscoring the urgency to elucidate the mechanisms of treatment resistance and to design more effective therapeutic strategies. Conventional cancer treatments, including cytotoxic chemotherapy, radiation therapy, and targeted therapy, have immunomodulatory effects in addition to direct cancer cell killing activities. Their clinical utilities in combination with immune checkpoint inhibitors (ICI) have been explored, aiming to achieve synergetic effects with improved and durable clinical response. Here, we will review the immunomodulatory effects of chemotherapy, targeted therapy, and radiation therapy, in the setting of ICI, and their clinical implications in reshaping modern cancer immunotherapy.